Sou dessas mulheres que só dizem sim : As mulheres descritas na poesia de Chico Buarque de Holanda - Lima, Roberto Gabriel Guilherme de (2009)
This dissertation approaches the question of gender as a vehicle of identity in contemporary discourse. It attempts to (de)construct the hegemonic masculine discourse, breaking with the binarism masculine/feminine and uses premises of the queer theory, which proposes post-modern literary discourses in relation to the notion of gender identity. In this context, we focus the discourses present in Chico Buarque s songs taken as feminine representations they contrast with songs of former songwriters trying to understand the break of the dichotomy masculine/feminine